2022
DOI: 10.5336/nurses.2021-85337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronavirus Fears of Nursing Students Receiving Online and Face-to-Face Training in Pandemic: Cross-Sectional Study

Abstract: the coronavirus disease-2019 (COVID-19) noted to be caused by severe acute respiratory syndrome-coronavirus-2, emerged in Wuhan city, Hubei Province, China. Since then, local and national governments have begun to take measures in social and economic areas in response to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In the relevant literature, there are studies that obtained similar results (4,5,22). In the study performed by Terkeş and Ateş (10) to compare the COVID-19 fear levels of nursing students who received online and face-to-face education, it was found that students generally had moderate levels of fear of COVID-19, and those students who had faceto-face education had higher levels of fear of COVID-19.…”
Section: Fear Of Covid-19mentioning
confidence: 84%
See 1 more Smart Citation
“…In the relevant literature, there are studies that obtained similar results (4,5,22). In the study performed by Terkeş and Ateş (10) to compare the COVID-19 fear levels of nursing students who received online and face-to-face education, it was found that students generally had moderate levels of fear of COVID-19, and those students who had faceto-face education had higher levels of fear of COVID-19.…”
Section: Fear Of Covid-19mentioning
confidence: 84%
“…While it was known that nursing students already experience high levels of anxiety and stress due to their nursing education, it was revealed that their stress and anxiety levels increased along with the COVID-19 pandemic (5)(6)(7)(8). The fast spread of COVID-19, which was a development that caught many individuals and systems off guard, and the lack of information about its control and treatment also led to fear in nursing students just as all active and prospective health workers (5,(8)(9)(10).…”
mentioning
confidence: 99%